FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI TIM PENILAI AMDAL STUDI KASUS PROVINSI SULAWESI UTARA - Langi, Dena Natalia; Sholihah, Qomariyatus; Parmawati, Rita (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2021)
EIA is part of several instruments to prevent pollution and environmental damage, and in order to improve its quality and effectiveness, EIA document will be assessed by the EIA Assessment Commission depending on its authority. The assessment ability of the EIA Assessment Commission is also influenced by perceptions, so it is necessary to analyze the influence of internal and external factors on the perception of the EIA Assessment Commission in North Sulawesi, so it can provide good suggestions and input for better regional development and towards environmental sustainability. The research sample were 57 respondents and then used in-depth interviews guided by the questionnaire to digging information. The data obtained were then analyzed using Partial Least Square (PLS) to observe the impact of internal and external factors on the perception of the EIA Assessment Commission. Internal factors including age, education level, and family responsibilities do not significantly affect the level of perception, while internal factors such as experience and integrity as well as all external factors have a significant effect on perception. Work experience has a strong impact on the perception of the EIA Assessment Commission to always support the environmental conservation movement and integrity have an impact on the emergence of rational and fair decision making Key words: EIA, Integrity, Assessment, Perception.